Women, Men and News: It's life, Jim, but not as we know it†. (26th April 2018) - Ross, Karen; Boyle, Karen; Carter, Cynthia; Ging, Debbie
Abstract : In the twenty-teens, there are increasing numbers of women occupying executive positions in politics, business and the law but their words and actions rarely make the front page. In this article, we draw on data collected as part of the 2015 Global Media Monitoring Project (GMMP) and focus on England, Scotland, Wales and the Republic of Ireland. Since the first GMMP in 1995, there has been a slow but steady rise in the proportion of women who feature, report or present the news (now at 24 per cent), but that increase is a mere 7 per cent over 20 years. Not only is there a problem with visibility but our data also suggest that when women are present, their contributions are often confined to the realm of the private as they speak as citizens rather than experts and in stories about health but not politics. Just over a third of the media professionals we coded were women and older women are almost entirely missing from the media scene. Citizens and democracy more generally are poorly served by a news media which privileges men's voices, actions and views over the other 51 per cent of the population: we surely deserve better.